Taking control : autonomy in language learning - Pemberton, Richard, 1957- (Book collections on Project MUSE., 1996)
TAKING CONTROL: Autonomy in Language Learning focuses on an area of language learning and teaching that is currently receiving an increasing amount of attention. The book, featuring 18 chapters from key figures around the world in the field of autonomous and self-access language learning, provides insightful coverage of the theoretical issues involved, and represents a significant contribution to research in this area.